Livestock-associated methicillin-resistant Staphylococcus aureus (MRSA) as causes of human infection and colonization in Germany. - Robin Köck (Public Library of Science (PLoS), 2013)
Pigs, cattle and poultry are colonized with MRSA and the zoonotic transmission of such MRSA to humans via direct animal contact, environmental contaminations or meat are a matter of concern. Livestock-associated (LA) MRSA are mostly belonging to clonal complex (CC) 398 as defined by multilocus sequence typing. However, MRSA of other clonal lineages including CC5, CC9 and CC97 have also been detected in livestock animals in Germany. Within the framework of a Dutch-German network project (EUREGIO), 14,036 MRSA isolated from clinical and screening specimens (January 2008 - June 2012) derived from human patients in hospitals as well as general or specialized practices in a German region characterized by a high density of livestock production, were subjected to S. aureus protein A (spa) sequence typing. The prevalence of putative LA-MRSA among the human MRSA isolates was determined by analyzing the detection of livestock-indicator (LI) spa types which had already been reported in German livestock. Overall, 578 spa types were detected among the MRSA isolates. LI spa types t011, t034, t108, t1451, t2011, t571, t1456, t1250, t1255, t1580, t2970, t2346, t1344, t2576, t2330 and t2510 (all of which are indicative for LA-MRSA CC398) accounted for 18.6% of all human isolates. The LI spa types t1430 (CC9), t3992 (CC97), t002 (CC5) and t007 (CC30) were found in 0.14%, 0.01%, 1.01% and 0.04% of all human MRSA isolates, respectively. LI spa types associated with CC398 represented 23% of all MRSA from screening samples and a varying proportion among isolates from clinical specimens ranging between 0% in cerebrospinal fluid, 8% in blood cultures and 14% in deep respiratory fluids. Our findings indicate that LA-MRSA are a major cause for human infection and stress the need for close surveillance. Although LA-MRSA CC398 predominates, the occurrence of putative LA-MRSA from other clonal lineages should be monitored.